Analisis Sikap Pegawai terhadap Perilaku Pelayanan Publik (Studi Kasus di BP2T Kabupaten Sragen dan Kabupaten Sidoarjo) - Puji Winarni; Ma'mun Sarma; Darwis S Gani; Soenarmo Hatmodjosoewito (Jurnal Penyuluhan, 2012)
The implementation of Quality Management System (ISO 9001) by BP2T in both Sidoarjo and Sragen Districts has been considered successful in transforming the existing paradigm of service which had been criticized as being irresponsive, untrustworthy, and not oriented toward public interest. The existence of service culture oriented toward public interest has been in doubt due to the prevailing perception that quality culture has not developed within the Government’s bureaucratic environment. This study has aimed at: 1) analyzing the Government employers’ attitudes toward the implementation of ISO 9001: 2) explaining the impacts of the attitudes on the service behaviors among those Government employers who are more responsive toward the public interest. The study shows that there has been a significant positive attitude among the employers toward the implementation of ISO 9001 which has, in turn, positively correlated with their responsive service to the public.Key words: ISO 9001, employees’ attitudes and behaviors, BP2T, Government employers